Quality Management of Teaching Materials at Atsaamenah Lil Arabiyyah Course Institute: Manajemen Kualitas Bahan Ajar di Institut Kursus Atsaamenah Lil Arabiyyah - Naili Nur Azizah; Ulfatul Mufidha; Fikri Haikal Ibrahim; Shofil Fikri (ELOQUENCE : Journal of Foreign Language, 2025)
Background: This study was motivated by the importance of teaching material quality management to ensure that the material complies with the quality, content standards, and competencies set out in the National Education Standards (SNP). However, the teaching materials used in a number of course institutions do not yet fully comply with these standards, so further study is needed. Based on interviews with the director of one of the course institutions, it was found that the teaching materials used were considered effective in supporting the achievement of student competencies, as evidenced by the improvement in their language skills. Therefore, this study aims to examine the suitability of the teaching materials used with the applicable standards. Purpose: The objective of this study is to analyze the quality of teaching materials and describe the implementation of teaching material quality management in Arabic language course institutions, particularly in terms of their compliance with National Education Standards. Method: The method used in this study is a descriptive qualitative type, with data collection in the form of interviews and documentation. Data analysis was conducted in several stages, namely data condensation, data presentation, and data verification. Results and Discussion: The research results indicate that the Al-‘Arabiyyah Baina Yadayk Volume 1 textbook at the Atsaamenah Lil Arabiyyah Course Institution meets the four aspects of instructional material quality according to the BSNP and its management aligns with National Education Standards. However, the low pass rate (33–40%) suggests that quality management implementation is not yet optimal due to a gap between competency standards and learning outcomes. Conclusions and Implications: In conclusion, the quality of the Al-‘Arabiyyah Baina Yadayk Volume 1 teaching materials and their quality management at the Atsaamenah Lil Arabiyyah Language Course Institute are in line with the National Education Standards. However, the low graduation rate of participants (33–40%) indicates that its implementation is not yet optimal. The implication is that continuous evaluation of the application of competency standards is needed so that quality